Predator and scavenger movements among and within endangered seabird colonies: Opportunities for pathogen spread. Issue 2 (3rd December 2019) - Gamble, Amandine; Bazire, Romain; Delord, Karine; Barbraud, Christophe; Jaeger, Audrey; Gantelet, Hubert; Thibault, Eric; Lebarbenchon, Camille; Lagadec, Erwan; Tortosa, Pablo; Weimerskirch, Henri; Thiebot, Jean‐Baptiste; et al.
Abstract: The spatial structure of host communities is expected to constrain pathogen spread. However, predators and/or scavengers may connect distant host (sub)populations when foraging. Determining whether some individuals or populations play a prominent role in the spread of pathogens is critical to inform management measures. We explored movements and epidemiological status of brown skuas Stercorarius antarcticus, the only avian terrestrial consumer native of Amsterdam Island (Indian Ocean), to assess whether and how they could be involved in the spread of the bacterium Pasteurella multocida, which recurrently causes avian cholera outbreaks in endangered albatross and penguin species breeding on the island. High proportions of seropositive and DNA‐positive individuals for P. multocida indicated that skuas are highly exposed to the pathogen and may be able to transmit it. Movement tracking revealed that the foraging ranges of breeding skuas largely overlap among individuals and expand all along the coasts where albatrosses and penguins nest, but not on the inland plateau hosting the endemic Amsterdam albatross Diomedea amsterdamensis . Considering the epidemiological and movement data, skua movements may provide opportunity for pathogen spread among and within seabird colonies. Synthesis and applications. This work highlights the importance of considering the behaviour and epidemiological status of predators and scavengers in disease dynamics because the foraging movements of individuals of such species can potentially limit the efficiency of local management measures in spatially structured host communities. Such species could thus represent priority vaccination targets to implement efficient management measures aiming at limiting pathogen spread and also be used as sentinels to monitor pathogen circulation and evaluate the effectiveness of management measures. Abstract : This work highlights the importance of considering the behaviour and epidemiological status of predators and scavengers in disease dynamics because the foraging movements of individuals of such species can potentially limit the efficiency of local management measures in spatially structured host communities. Such species could thus represent priority vaccination targets to implement efficient management measures aiming at limiting pathogen spread and also be used as sentinels to monitor pathogen circulation and evaluate the effectiveness of management measures. Picture: Marine Bely, IPEV. Translated Abstract Résumé: La circulation d'agents infectieux dans les populations sauvages peut être fortement contrainte par la structuration spatiale de leurs communautés d'hôtes. Cependant, de par leurs comportements alimentaires, certains prédateurs et/ou charognards peuvent connecter des (sous‐)populations spatialement éloignées. Identifier les individus ou populations susceptibles de jouer un rôle prépondérant dans la dissémination d'agents infectieux pathogènes est un élément clé pour la compréhension, et éventuellement le contrôle, des dynamiques épidémiologiques dans les populations sauvages. Dans ce contexte, nous avons suivi les déplacements et statuts épidémiologiques de labbes subantarctiques ( Stercorarius antarcticus ), uniques prédateurs et charognards terrestres aviaires natifs de l'île Amsterdam (Océan Indien), afin d'évaluer leur implication dans la dissémination de Pasteurella multocida, la bactérie responsable d'épizooties récurrentes de choléra aviaire affectant les albatros et gorfous de l'île. Les fortes proportions d'individus positifs à P. multocida par sérologie et PCR indiquent que les labbes sont fortement exposés à la bactérie et susceptibles de la transmettre. Par ailleurs le suivi des déplacements d'individus reproducteurs a révélé que les zones de recherche alimentaire individuelles des labbes se superposent et s'étendent tout le long de la partie de côte occupée par les albatros et les gorfous. Au contraire, le plateau central où se reproduit l'albatros d'Amsterdan ( Diomedea amsterdamensis ), espèce endémique de l'île, ne semble pas visité par les labbes en reproduction. Compte tenu des données épidémiologiques et écologiques présentées les labbes sont susceptibles de contribuer à dissémination d'agents infectieux au sein et entre des colonies d'oiseaux marins menacés d'extinction. Synthèse et applications . Cette étude met en évidence l'importance de prendre en considération le comportement et le statut épidémiologique des prédateurs et charognards lors de la mise en place de programmes de contrôle de dynamiques épidémiologiques. En effet le comportement alimentaire de telles espèces peut limiter l'efficacité des mesures locales malgré l'apparente structuration spatiale des populations affectées. Prédateurs et charognards peuvent ainsi représenter des cibles prioritaires pour les programmes de vaccination visant à limiter la dissémination d'agents infectieux pathogènes mais également être utilisés comme sentinelles pour en suivre la circulation et évaluer l'efficacité des programmes de contrôle.